PENGARUH BELANJA DAERAH SEKTOR PARIWISATA DAN PERDAGANGAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DAN PENDAPATAN ASLI DAERAH DI KOTA BONTANG - Silverawaty Silverawaty; Eny Rochaida; Juliansayah Juliansayah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the effect of regional government expenditure in the tourism and trade sectors on non-oil and gas Gross Regional Domestic Product and its impact on Local Own-Source Revenue (PAD) in Bontang City. The research adopts a quantitative appr oach using path analysis to identify causal relationships among variables. The data consist of ten years of secondary time-series data obtained from the Central Bureau of Statistics and local government financial documents. The results indicate that government expenditure in the tour ism sector has a positive and significant effect on non-oil and gas GRDP. In contrast, expenditure in the trade sector shows a positive but insigni ficant effect on non-oil and gas GRDP. Furthermore, non-oil and gas GRDP has a positive and significant effect on PAD. Path analysis reveals an indirect effect of tourism sector expenditure on PAD through nonoil & gas GRDP, suggesting that increased tourism spending stren gthens local economic activity and enhances fiscal capacity. However, the indire ct effect of trade sector expenditure on PAD through GRDP is found to be insigni ficant. These findings highlight the strategic role of the tour ism sector as a key driver of regional economic growth & local fiscal sustainability